4(2x+4)-6=-2(-5-4x)

Simple and best practice solution for 4(2x+4)-6=-2(-5-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x+4)-6=-2(-5-4x) equation:



4(2x+4)-6=-2(-5-4x)
We move all terms to the left:
4(2x+4)-6-(-2(-5-4x))=0
We add all the numbers together, and all the variables
4(2x+4)-(-2(-4x-5))-6=0
We multiply parentheses
8x-(-2(-4x-5))+16-6=0
We calculate terms in parentheses: -(-2(-4x-5)), so:
-2(-4x-5)
We multiply parentheses
8x+10
Back to the equation:
-(8x+10)
We add all the numbers together, and all the variables
8x-(8x+10)+10=0
We get rid of parentheses
8x-8x-10+10=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| (3x-4)=15+45 | | 3y+4{y-2}=85 | | 3(-x+2)=4x+6 | | 10w+19+3w=6(9+w)=14 | | 1.2x+.085X=208000 | | 7-5x=31 | | 180=2x+x+132 | | 49-3m=14m+14 | | y=10+0.8Y+100 | | 180=2xx+132 | | 7+-5x=31 | | 1.2x+1.085X=208000 | | 3(7-2x)-5(3-x)=15-2(4x-1) | | 180=2x+x+1#2 | | 11=-a+7 | | 5(3x-1)=-0.5(4x-2) | | 1.2x*1.085=208000 | | 5(2x-7)-4(3-4x)=7-2(x-4) | | 30+60+x=120 | | 2(x-8)+3(3x-5)=4-7x | | a=1/2(4.8+7.2)3.5 | | 4(2x+5)-3(x-4)=-2(x+1) | | 4m-7=7 | | 15x+9-4x+3=89 | | 20.3*2=x | | -2(x-4)+3(7-x)=4(x-1) | | -11r+1(6r+4)=44+10 | | x+4.9=^.1 | | -6-192=11x+80 | | 14-5x=2x+3 | | 3(4x+3)=-3(5x-4)-2x | | 2x-8=1/2x-2 |

Equations solver categories